A RELATIONSHIP BETWEEN READING AND WRITING PERFORMANCE - Yani Adyawardhani (Jurnal Bahasa Inggris Terapan, 2016)
The present study is investigating the relationship between students’ performance in reading and writing after they have learned from the Subjects of Reading 3 and Essay Writing. The result is a positive correlation although it is not a strong one. There may be some variables that are not studied; therefore it needs a further study to look into the relationship. Keywords: reading performance, writing performance, relationship between reading and writing